2012
DOI: 10.3349/ymj.2012.53.5.1054
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplantation for Bronchiolitis Obliterans after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Bronchiolitis obliterans (BO) is a late onset complication of allogeneic hematopoietic stem cell transplantation (HSCT), and treatment outcome is dismal if it does not respond to immunosuppressive therapy. A 21-year-old male diagnosed with acute myeloid leukemia received an allogeneic HSCT from human leukocyte antigen- identical sibling donor. Twenty one months after transplantation, he developed progressive dyspnea and was diagnosed BO. Despite standard immunosuppressive therapy, the patient rapidly progresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The authors found similar effects of ILA therapy on CO 2 removal, correction of acidosis, and the resulting reduction of ventilator settings, when compared to our data [6]. In the meantime, several centers have reported on a total of 55 hypercapnic patients who underwent ECCO2-R by a/v ILA as attempted bridge to LTX [6][7][8][9]30,31]. However, unfortunately important outcomes including rate of successful LTX, short-and longterm survival have not been indicated in several of these reports ( Table 5).…”
Section: Discussionsupporting
confidence: 83%
“…The authors found similar effects of ILA therapy on CO 2 removal, correction of acidosis, and the resulting reduction of ventilator settings, when compared to our data [6]. In the meantime, several centers have reported on a total of 55 hypercapnic patients who underwent ECCO2-R by a/v ILA as attempted bridge to LTX [6][7][8][9]30,31]. However, unfortunately important outcomes including rate of successful LTX, short-and longterm survival have not been indicated in several of these reports ( Table 5).…”
Section: Discussionsupporting
confidence: 83%
“…Despite the many clinical studies on treatment strategies for BO after HSCT, there is still no definitive treatment. Treatment of BO consists of corticosteroid and immunosuppressive drugs such as cyclosporine A or tacrolimus [9]. When the conventional immunosuppressive treatment is ineffective, the 2-year survival rate is 20% [10].…”
Section: Discussionmentioning
confidence: 99%
“…When the conventional immunosuppressive treatment is ineffective, the 2-year survival rate is 20% [10]. A few papers have recently reported on lung transplantation (LT) for BO complicated by HSCT, and suggested LT as an effective therapy for respiratory failure secondary to BO [9]. However, LT leads to high post-operative risk of rejection and infection, and finding a suitable lung donor is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…94 Some case series were published during the next years using the same device or the Decap Smart © system. 9599 Effective correction of acidosis was possible in nearly all cases, while outcome was less convincing. Our own group published a series of 20 patients undergoing ECCO 2 R as a bridge to LTX.…”
Section: Indications For Ecco2rmentioning
confidence: 99%